Potential mechanisms and clinical applications of static magnetic field therapy in glioma - Sun, Ziyu; Zhu, Kairui; Zhao, Wenxuan; Fei, Xi-feng; Shi, Lei; Zhang, Yong (Frontiers in Neurology, 2025)
Static magnetic field (SMF) therapy, a non-ionizing and non-invasive treatment modality, has garnered increasing attention in glioma research. Gliomas, particularly glioblastoma (GBM), represent one of the most aggressive malignancies of the central nervous system, with limited therapeutic options and significant treatment-related toxicity. Emerging evidence suggests that SMF therapy exerts antitumor effects by inducing apoptosis, inhibiting cell proliferation, and modulating the tumor microenvironment, while minimizing damage to surrounding healthy tissues. Despite promising preclinical findings, research on SMF therapy remains in its early stages, and its precise mechanisms, clinical efficacy, and safety require further elucidation. This review summarizes current advancements in SMF therapy for gliomas, explores its potential as a standalone or adjunctive treatment, and discusses future research directions to optimize its therapeutic application.